Food and sustainability: meat consumption and vegetarianism in Brazil and the United Kingdom - Wolstenholme, Emily; Duarte, Tiago Ribeiro; Teixeira, Thaís Rozas; Whitmarsh, Lorraine; Poortinga , Wouter (Sustainability in Debate, 2024)
There is a growing literature on meat consumption and reduced meat diets, given the negative impacts of meat on the environment. However, much of the literature has focussed on global North countries, limiting cross-cultural generalisability and overlooking the role of cultural differences in motivating food choices. The present paper provides a cross-cultural comparison of the motivations for meat consumption and vegetarianism in Brazil and the United Kingdom. This was done by conducting a total of 63 semi-structured interviews with meat-eaters, vegetarians, and vegans in Brazil (n = 41) and the UK (n = 22). The data was analysed thematically and the findings were compared across the participant samples. The findings showed that meat consumption was similarly motivated and justified in each country through the 4 N’s of justification for meat consumption. However, participants’ experiences of reducing meat consumption varied between the two countries, influenced by distinct motivations, aversions, and constraints. In the UK, price served as a motivation for choosing meatless meals, whereas in Brazil it acted as a constraint to reducing meat consumption. Additionally, in the UK, disgust was identified as a significant aversion particularly towards eating parts of meat that visibly resembled the animal of origin — a sentiment not observed in the Brazilian sample. Lastly, while environmental concerns were not a primary reason for adopting a plant-based diet in either country, they often became a significant motivator for maintaining it after dietary change.